Legal Certainty in Hotel Acquisitions Through Sustainable Tourism Investment Harmonization - Ayu Putu Eka Susanti Dewi; I Nyoman Sujana; I Wayan Rideng (International Journal of Community Service (IJCS), 2026)
Legal uncertainty surrounding hotel company acquisitions by foreign investors persists because corporate, investment, tourism, environmental, and land regulations remain fragmented and insufficiently coordinated. This study investigates the causes of regulatory inconsistency and proposes a harmonized legal framework capable of strengthening legal certainty while promoting sustainable tourism investment. A normative legal research design was employed using statutory, conceptual, and comparative approaches, supported by qualitative analysis of primary and secondary legal materials. The findings demonstrate that existing regulations primarily emphasize transactional legality and investment facilitation without adequately integrating sustainability principles into acquisition governance. As a result, overlapping authorities and disconnected legal provisions continue to weaken regulatory coherence and investor confidence. The principal novelty of this research lies in developing a harmonized regulatory model that integrates legal substance, institutional coordination, and legal culture throughout the pre-acquisition, approval, post-acquisition, and monitoring stages. This model offers a comprehensive governance framework that balances investment certainty with environmental protection, socio-cultural preservation, and sustainable tourism development. Future studies should empirically evaluate the implementation of this model across different jurisdictions and tourism destinations to assess its practical effectiveness. Overall, regulatory harmonization provides a strategic legal foundation for achieving coherent investment governance and sustainable tourism development.